Structural characterization of electrodeposited nickel-iron alloy films - Marita, Yusrini; Yaacob, Iskandar Idris (Trans Tech Publications, 2010)
Nickel-iron nanocrystalline alloy films were prepared on copper substrates by electrochemical deposition at various current densities of 6, 9.7, 11.5 and 15.2 A dm-2. X-ray diffraction measurements confirmed that all nickel-iron alloy films formed have face-centered cubic structure. The structural parameters such as the lattice constant, crystallite size, microstrain and dislocation density were determined for the nickel-iron alloy films. The crystallite size of the films reduced from 17 to 12.9 nm when the current densities were decreased. The reduction in crystallite size increased the dislocation density. Magnetic property measurements using alternating gradient magnetometer indicated that these alloys were ferromagnetic. The saturation magnetization Ms of nickel-iron alloy films increased with decreasing deposition current density, which was attributed to the increase of iron content. Nickel-iron alloy film prepared at deposition current density of 6 A dm-2 showed the maximum value of Ms. The coercivity of nickel-iron alloy films increased with decreasing current density, which was likely caused by reduction in crystallite size. © (2010) Trans Tech Publications.